(untitled) (SCIENCE TIME JOURNAL, 2025)
The article explores the critical role of effective communication within military contexts, particularly focusing on the challenges posed by translation and language barriers. The author discusses how specialized military terminology, jargon, and cultural nuances can complicate communication between diverse military forces, especially in multinational operations. Key themes include the importance of accurate translation in maintaining operational effectiveness and the potential consequences of miscommunication in high-stakes environments.